OS PRECEDENTES JUDICIAIS E O CONSENSO SOBREPOSTO DE JOHN RAWLS - Malanchini, Reichiele Vanessa Vervloet de Carvalho (2020)
The validity of the Civil Procedure Code of 2015 (13.105 / 2015) reorders the way of operating Brazilian civil procedural law, bringing a transformation to the procedural system, namely: institution of a model of formally binding normative judicial preced